"Ochroniarze" kontra determinizm historyczny. Walka na wartości w "Turnieju Reporterów 74" białostockich "Kontrastów" = "Protectors" vs. historical determinism. A battle of values in "1974 Non-fiction Contest" held by Białystok`s "Kontrasty" Magazine - Sokołowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The "Kontrasty" Magazine, published in Białystok, became a newly found forum for reporters since its 1975, Vol. 4 issue. That was the result of a writing competition on Podlasie`s post-war history, announced that same year. Awarded works dealt with various aspects of Polish rural life such as the migration of young generations of farmers to cities. Many of them were written along the lines of socialist propaganda of the economic success marking the period of the early 1970s. Here we focus our attention specifically on Wojciech Giełżynski`s feature article "New things are coming to Augustow".
Keywords: publicystyka; socjalizm; propaganda; PRL; ekolodzy; journalism; socialist system; ecologists